Subgrain dynamics during recovery of partly recrystallized aluminum. (15th February 2020) - Ahl, S.R.; Simons, H.; Detlefs, C.; Jensen, D. Juul; Poulsen, H.F.
Abstract: The recovery dynamics of 498 individual subgrains within the non-recrystallized matrix of a 50% recrystallized aluminum sample is studied using high resolution X-ray diffraction at a synchrotron source. The subgrains' change in size, orientation, axial strain and internal disorder are monitored as functions of temperature. The subgrains are surprisingly active, and the individual subgrains exhibit markedly different growth kinetics. Contradictory to common knowledge we find that the individual subgrains' sizes change significantly even though the average size remain constant. Furthermore we observe no correlation between subgrain size and growth rate. An analysis of the volume changes of the individual subgrains indicates a broad spectrum of critical temperatures above which the subgrains grow or shrink. Possible mechanisms are discussed and related to relaxation of local stresses. Graphical abstract: Image, graphical abstract